Improving Efficiency Evaluation in Tourism Analysis Weight Restrictions Models and Value Judgments - Oliver, María Pilar Alberca (2022)
The aim of this study is to analyze the operational efficiency of tourism firms using weights-restricted data envelopment analysis (DEA) in a mathematical optimization framework. The use of weight restrictions has been applied in several studies on efficiency and performance evaluation, in order to account for the decision maker's information. In this study, a nonstandard approach to operational efficiency evaluation is applied in an attempt to overcome certain limitations in tourism analysis— namely, the fact that the analyst may choose to consider only a few rather than all of the input variables. One of the main findings of this study is that total weight flexibility can lead to nonrational weights due to the fact that certain inputs are effectively ignored. Furthermore, total weight flexibility can result in too many units being assessed as efficient, reducing the discriminatory power of the model. This problem can be solved by applying weight restrictions. A first practical implication is that the weighted DEA model yields better efficiency estimations. Moreover, since a high number of efficient units could be considered an unrealistic result, the findings of this study demonstrate that the choice of weighted or restricted DEA model produces more accurate efficiency results.